RELEVANSI PEMIKIRAN PENDIDIKAN ISLAM HARUN NASUTION DENGAN PENDIDIKAN ERA MODERN DI INDONESIA - Diah Rusmala Dewi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2019)
This article aims to analyze Harun Nasution’s thoughts on education and its relevance to the modern world, especially in Indonesia. The method used in this research is literature study where the author tries to find, compile and analyze various information through various related sources. The results of this study explain that according to Harun Nasution, the backwardness of Muslims in Indonesia is caused by the Islamic education system which only focuses on the teachings of worship and fiqh which have implications for Islamic teachings which are interpreted as narrow and rigid teachings so that reforms in the world of Islamic education are needed by paying attention four important things, namely: (1) the educational curriculum should be prepared by taking into account the moral aspects, development and growth of students’ thought processes, (2) the use of educational methods should emphasize the cultivation of moral education so that good morals are formed in children in addition to the delivery of material, (3) educators should have various competencies and constantly improve their quality, (4) religious education should produce students or students who religious spirit, not just religious knowledge. The positive impact expected in this article emphasizes the importance of moral aspects to be instilled in students to answer the problem of moral decline that is increasingly prevalent in this modern era.